THE PSYCHOLINGUISTICS OF NEOLOGISM: HOW WE PROCESS AND UNDERSTAND NEW WORDS - Abdullaeva Shakhlo Sayfievna (Western European Studies, 2024)
Neologisms, or newly coined words, are a constant feature of language evolution. This article delves into the cognitive processes involved in understanding and incorporating neologisms into our mental lexicon. We explore how factors such as semantic transparency, morphological complexity, and contextual cues influence neologism processing. By examining relevant research, we shed light on the mechanisms underlying neologism comprehension and the neural correlates of this process. Understanding these mechanisms can provide valuable insights into language acquisition, cognitive development, and the dynamics of language change.
Keywords: neologism; language processing; cognitive psychology